Lactate dehydrogenase to albumin ratio as an independent factor for 28-day mortality of neonatal sepsis - Xiaohong Xia; Shengfeng Qiu; Xiangjun Cheng; Mengxiao Xie; Jun Zhou (Scientific Reports)
Abstract Neonatal sepsis significantly contributes to infant mortality rates. The absence of predictive markers has hindered timely clinical intervention, leading to elevated mortality. This study aimed to assess the prognostic relevance of the lactate dehydrogenase (LDH)-to-albumin ratio (LAR) in neonatal sepsis. A retrospective examination was conducted on a cohort of 130 neonates diagnosed with sepsis. Admission laboratory data were gathered. The optimal threshold for LAR was established using receiver operating characteristic curve analysis. Both univariate and multivariate analyses were performed to gauge the predictive efficacy of LAR. A statistical disparity in LAR was noted between survivors and non-survivors (p < 0.001). Multivariate analysis confirmed that LAR serves as an independent risk determinant for neonatal sepsis (Hazard ratio [HR] 11.236, 95% Confidence interval [CI] 3.311–38.462, p < 0.001). ROC analysis indicated that the area under the curve for LAR was 0.806 across the entire cohort, 0.842 for early-onset sepsis, and 0.737 for late-onset sepsis. Moreover, with a cutoff value set at 23.72, LAR exhibited a prediction specificity of 88.2% and sensitivity of 70.0%. Our research indicates that elevated admission LAR is a negative prognostic indicator in neonatal sepsis, suggesting its potential as a valuable biomarker in clinical settings.